Performance evaluation of bio-lubricants in strip drawing and deep drawing of an aluminium alloy. Issue 1 (2nd January 2022) - Prakash, Ved; Kumar, D. Ravi
ABSTRACT: With the increasing awareness and concerns towards the detrimental impact of mineral-oil-based lubricants, a step forward is crucial to replace them with benign environment-friendly lubricants. Bio-lubricants, due to their intrinsic lubricant properties attributed to the presence of long chain fatty acids, have an immense potential to be utilised as green lubricants and could be promising substitutes for the mineral oil-based lubricants. In this work, the performance evaluation of three bio-lubricants (Cottonseed, Karanja, and Jatropha oils) is carried out by applying in strip drawing and deep drawing experiments. The strip draw tests are conducted to determine the coefficient of friction, whereas the effectiveness of the bio-lubricants in the deep drawing are examined evaluating the drawability, thinning, drawing load and surface finish. The obtained results are compared with a mineral-oil-based lubricant and a water soluble paste. All the three bio-lubricants are found to perform well in comparison to mineral-oil-based lubricant in terms of resulting friction coefficient, drawability, and thinning at low normal pressure. Cottonseed oil is found to be better than the other two bio-lubricants. However, with an increase in normal pressure, the lubricating performance of bio-lubricants decreased significantly which can be addressed by adding extreme pressure additives.